Assessment of dynamic properties of a crowd model for human–structure interaction modeling. (15th April 2015) - Salyards, Kelly A.; Hua, Yue
Highlights: Experimental modal analysis was applied to an occupied laboratory structure. Analytical modeling using recommended occupant models was performed. Confirmation of active occupant model for standing with bend knees crowd posture. Confirmation of newly proposed occupant model for standing straight crowd posture. Unable to confirm passive occupant model for seated occupants. Abstract: Occupants of a structure are thought to behave as a dynamic spring-mass-damper system interacting with the structure through a phenomenon known as human–structure interaction. Understanding this interaction is critical for vibration serviceability as neglecting to account for its effects may result in an overestimation of the dynamic response of a structure, and as a result, a more costly structural design. An experimental study has been performed and the results are compared with analytical models constructed with the parameters proposed by the Joint Working Group (JWG) in the United Kingdom for modeling occupants as a spring-mass-damper system. The results indicate that the parameters of the "active and mostly standing" crowd model satisfactorily represent the dynamic response of the structure with passive occupants standing with bent knees. However, the parameters of the "predominantly seated" crowd model did not adequately simulate the dynamic response of the structure when passive occupants were seated on the structure. A new set of parameters for passive standing occupants, not specifically addressed by the Joint Working Group, was also assessed yielding acceptable results. This study asserts that at least three different models, with varying parameters, are necessary to thoroughly understand the effects of human–structure interaction. The experimental results confirm the applicability of the JWG parameters for active occupants and verify the appropriateness of previously proposed parameters for modeling the passive standing occupant.